Digital finance, financing constraints, and regional trade development - Zheng, Minyu (Elsevier Ltd, 2025)
This study explores the close connection and impact mechanism between digital finance and the development of import and export trade in various regions of China. The research finds that the development of digital finance significantly promotes the growth of export trade in various regions. Meanwhile, digital finance enhances the competitiveness of enterprises by alleviating their financing constraints, thereby boosting regional trade development. In addition, digital finance encourages enterprises to increase their investment in scientific and technological research and development (R&D), driving an increase in regional R&D intensity and subsequently promoting regional trade development. The results of heterogeneity analysis indicate that the impact of digital finance development on export scale plays a significant promoting role in the western region, but the effect is not significant in the eastern and central regions.